Influence of Shopping Bags Carrying on Human Responses While Walking. (27th June 2018) - Ramadan, Mohamed Z.; Khalaf, Tamer M.; Ragab, Adham M.; AbdElgawad, AbdElatty A.
Abstract : Shopping as a daily activity that involves carrying shopping bags in hands might be associated with risk factors contributing to the development of low back pain (LBP) and strains and sprains in the upper extremity. A three-way repeated measures experiment was conducted for the purpose of the study. The independent variables were holding style, carrying technique, and shopping bags' weights. The dependent variables were cardiac cost, muscles' activities as a percentage of their maximum voluntary contraction's EMG (%MVC), peak plantar pressure (PPP), and discomfort rating. Carrying grocery bags with both hands to the sides of the body using shopping bags' holder was favorable and advantageous to other carrying conditions in terms of less cardiac cost, less %MVC, less peak plantar pressure, and less discomfort. It is useful to carry grocery bags close to the body with both hands using holders that are available in the local market.